185 CURRENT CHALLENGES IN MANAGING MULTIMORBID OLDER PATIENTS WITH ATRIAL FIBRILLATION – A PAN-EUROPEAN PERSPECTIVE. (25th October 2022) - Lee, G; Baker, E; Desteghe, L; Heidbuchel, H; Merino, J; Collins, R
Abstract: Background: Atrial Fibrillation (AF) is the most common cardiac arrhythmia and associated with a substantial burden to patients and health systems globally and its prevalence is increasing as the population ages. Methods: An online survey was distributed as part of a Horizon 2020 project (EHRA-PATHS) with the aim of evaluating how AF multimorbidity is currently addressed by clinicians, to characterize the treatment structure and to assess current interdisciplinary management of multimorbid AF. The survey included 21 questions and free-text option for comments on detection, assessment and management of AF-related comorbidities. Results: A total of 451 responses were received with 339 responses eligible for inclusion with the highest response rate from United Kingdom, Spain and Ireland (n=149, 44%). From all responses, 221 were male (66%), 300 (91.5%) were physicians and 196 (57.8%) were working in academic university teaching hospitals. Half of the respondents managed between 20 to 50 patients per month with multimorbid AF. The survey revealed varying rates of specialist services and referral to these services such as diabetes and heart failure across Europe. Academic university teaching hospitals offered greater numbers of specialist services compared to non-teaching hospitals (e.g. anticoagulation clinic 92 (47%) vs 50 (35%), p<0.03). 67% (n=227) of respondents reported that approximately 40% of patients with multimorbid AF need onwards referral to other specialist clinicians. Barriers to referring to specialist services for AF comorbidities were identified and included lack of integrated care model (n=174, 51%), organisational or institutional issues (n=145, 43%) and issues with patient adherence (n=126, 37%). Respondents identified areas where patient outcomes could be improved: better access to patient lifestyle modifications; improved organisation flexibility to enable innovation; greater access to evidence-based guidelines; and better interdisciplinary collaboration. Conclusion: The survey demonstrated the need for systematic, integrated management of AF-related comorbidities in older people and the results will inform the next stage of the EHRA-PATHS project.